Improving Third-Grade Students’ Animal Vocabulary Retention through Flashcard Media: A Case Study at Elementary School - Pipit Ertika Daristin; Elda Yulia Ryandini; Angella Novitaningrum; Dias Tiara Putri Utomo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Vocabulary development is a fundamental component in early English language learning, especially for young learners in elementary school, yet third-grade students often struggle to retain new vocabulary due to limited exposure and the use of less engaging instructional media. This qualitative case study investigates the role of flashcards in enhancing animal vocabulary retention among third-grade students at Elementary School through the implementation of a custom-designed teaching module that integrates visual flashcards into interactive learning activities such as recognition drills, pronunciation practice, matching games, and creative labeling tasks. Data were collected through classroom observation, document analysis of the instructional module, and teacher reflection. The findings demonstrate that flashcards significantly increased students’ attention, enthusiasm, and willingness to participate orally, as picture–word associations helped students recall vocabulary more confidently and accurately. Game-based learning fostered collaboration and deeper memory retention, while the creative tasks enabled students to apply vocabulary in written form, indicating meaningful learning transfer. Additionally, flashcards supported inclusive learning by providing visual cues that assisted students with lower proficiency while encouraging higher-performing students to extend their vocabulary knowledge. Overall, the study concludes that incorporating flashcards into a structured and engaging teaching design is an effective strategy to improve English vocabulary retention among young learners.